Association between Physical Activity Levels in Different Domains and Cardiac Autonomic Modulation in Breast Cancer Survivors: A Cross-sectional Study - Palma, Mariana R. [UNESP]; Vanderlei, Luiz Carlos M. [UNESP]; Tosello, Giuliano; Fregonesi, Cristina [UNESP]; Ribeiro, Fernanda E. [UNESP]; Cucato, Gabriel G.; Ritti-Dias, Raphael M.; Tebar, William R. [UNESP]; Christofaro, Diego Giulliano Destro [UNESP] (Wolters Kluwer, 2024)
Background Breast cancer survivors frequently present cardiac autonomic dysfunction. Physical activity (PA) has been associated with better cardiac autonomic modulation (CAM) in breast cancer survivors. Objective This study aimed to analyze the association between CAM and PA levels performed in different domains (work and occupation, sport and exercise, and leisure time and commuting) in breast cancer survivors. Methods This is a cross-sectional study with 99 breast cancer survivors (age, 55.3 ± 10.4 years). Cardiac autonomic modulation was assessed by heart rate variability, and PA levels at work and occupation, sport and exercise, and leisure time and commuting were assessed using the Baecke PA questionnaire. The sum of these 3 domains provided the total PA. The Mann-Whitney test was used to compare CAM between active and inactive women in different domains of PA. Results Cardiac autonomic modulation was similar between active and inactive women in the different domains (P >.05). However, when considering the total PA, active breast cancer survivors presented higher SDNN (average standard deviation of all normal RR intervals) (20.0 ± 13.4 vs 28.8 ± 14.0; P =.008) and SD2 (standard deviation of the long-term intervals between consecutive heartbeats) indices (29.2 ± 17.3 vs 38.7 ± 19.9; P =.005) compared with their inactive counterparts. Conclusion Breast cancer survivors with higher total PA presented better CAM compared with their less active peers. Implications for practice The results of this study are promising and show the importance of increasing PA levels in different domains for the maintenance of cardiovascular health among breast cancer survivors.
Keywords: Autonomic nervous system; Breast neoplasm; Exercise; Heart rate